Computational linguistics and temporal perspective. (7th December 2016) - Johnson, Austin
Abstract : This paper presents three studies which utilize Latent Semantic Analysis to investigate the effects of temporal perspective on the development of semantic information within a text. This project comprises a study in the quantitative phenomenology of speech with the goal of modeling how a discourse participant might experience a speech event in real time. The first study presents two short texts which demonstrate the constructs of temporal perspective. The second study tests for differences in semantic development according to temporal perspective across a corpus of 26 texts. The third study examines the occurrence rate at which a section of text causes an increase in semantic similarity within one temporal perspective and a decrease (or no change) in the other. The results support the hypothesis that the development of semantic information within a text differs according to one's temporal perspective.